Regional changes in the prevalence of Parkinson’s disease over a ten-year period in the state of Texas - Sean G. Young; Kathryn Elwell; Christopher R. Watts (Clinical Parkinsonism & Related Disorders)
Introduction: Region specific epidemiological knowledge is needed to better help government and private entities plan and develop interventions to address accelerating diagnoses of Parkinson’s disease (PD). We measured the within-state prevalence patterns of PD within the state of Texas, United States, over a ten-year period to include factors of sex and race/ethnicity, with a specific focus on county and regional patterns. Methods: Publicly available data from the State of Texas Outpatient Public Use Data File (PUDF) evaluated for the years 2012 and 2022. Individuals with a PD specific diagnosis code were included. Age group, race, ethnicity, sex, and county of residence were used to calculate state and county case counts for the years 2012 and 2022. Spatial cluster analysis was applied to assess concentrations of diagnoses across Texas. Results: Prevalence rates of PD increased substantially in Texas from 2012 to 2022, especially among those aged 65 and older and Hispanics. Males had a higher prevalence rate in both years, though both sexes doubled their prevalence over the ten-year period. Spatial cluster analysis showed changes in diagnosis concentration, from the central and northeastern regions to the southwestern border region. Conclusion: Outpatient diagnoses of PD increased substantially from 2012 to 2022. Spatial distribution of PD risk evolved over the decade; such that risk for PD was greatest in the southwestern region of Texas in 2022 compared to all other areas. Prevalence trends in Texas mirror global trends for PD and should inform prevention and intervention strategies in the future.